Digital poverty : Latin American and Caribbean perspectives (IDRC OttawaCA, 2007)
Seeks to initiate the leap towards a new perspective on ICT access, and to develop an analytical framework that examines the critical variables involved in effective ICT adoption in developing regions of the world.
Keywords: INFORMATION TECHNOLOGY